Analytic Hierarchy Process (AHP) As An Assessment Approach For Architectural Design: Case Study of Architectural Design Studio - Timuçin Harputlugil (Iconarp International Journal of Architecture and Planning, 2018)
Architectural design is an effective decision-making activity based on problem solving. Within this context, assessment of architectural design is complex. This complexity is not based on content and volume of problems, but also heterogeneity and uncertainty of information provided for assessment, subjective approaches, and a large number of the criterion for assessment. To solve the problems stated, within the content of this article, assessment methodology based on Analytic Hierarchy Process (AHP) – a Multi Criteria Decision Making(MCDM) methodology- supporting an effective comparative analysis among the alternative projects based on determined criterion is applied. The methodology is implemented with a case study of one of the design studios of Çankaya University with observation, research and assessment of the whole education term.